NATIONAL AND NON-TRADITIONAL MEDICINE IN UKRAINE: MECHANISM OF LEGAL REGULATION - Ямненко, Тетяна Михайлівна; Желяк, Аліна Андріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Objective: to define the term «traditional and alternative medicine», to explore the mechanism of legal regulation of traditional and alternative medicine. Research methods: logical, formal-dogmatic, comparative-legal, etc. Results: definition of the term «folk and non-traditional medicine», study of the mechanism of legal regulation of folk and non-traditional medicine. Discussion: possibilities of applying different doctrinal approaches to explaining the concepts of folk and non-traditional medicine and applying the legal mechanism to these concepts. Non-traditional medicine in Ukraine is an independent field of medical business. Many clinics, along with traditional forms of patient recovery, use traditional medicine methods. There are many alternative therapies that need close scrutiny by the state. For this reason, documentary support for activities in the field of alternative medicine is a complex legal issue. According to the Fundamentals of the Ukrainian legislation on health care №2801-XII of 19.11.1992, folk medicine (healing) - methods of healing, prevention, diagnostics and treatment based on the experience of many generations of people, established in folk traditions and do not need state registration. Thus, the legislator defined the concept of «folk medicine», and the term «unconventional medicine» was out of the legal field. Ukrainian regulations do not contain a list of techniques that refer to traditional or alternative medicine. At the same time, in the Nomenclature of Medical Specialties, approved by the order of the Ministry of Health of Ukraine No. 359 of 19.12.1997, there is a direction «Folk and non-traditional medicine». In fact, these terms have been intertwined, and often healing is a unifying concept of non-traditional forms of treatment. Each of us chooses to whom he gives the right to save his health - folk medicine or academic. The main task of the legislator - to clearly define the subject of the criteria and objectives of true folk and non-traditional medicine, to distinguish them from the dubious unconventional practice of home-grown «healing».